2015
DOI: 10.1016/j.jnoncrysol.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness of calcium–silicate–hydrate from molecular dynamics simulations

Abstract: Cement is the most widely used manufacturing material in the world and improving its toughness would allow for the design of slender infrastructure, requiring less material. To this end, we investigate by means of molecular dynamics simulations the fracture of calcium-silicate-hydrate (C-S-H), the binding phase of cement, responsible for its mechanical properties. For the first time, we report values of the fracture toughness, critical energy release rate, and surface energy of C-S-H grains. This allows us to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
112
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(131 citation statements)
references
References 56 publications
12
112
2
Order By: Relevance
“…It follows from theoretical works (e.g. Ghebrab and Soroushian [11]) that CH crystal pull-out raises the values of pure C-S-H to much higher values, 16.9-283 J/m 2 , which is in relation to our findings, whereas the pure C-S-H fracture energy ranges only between 0.38-2.85 J/m 2 [11,12].…”
Section: Fracture Energy and Fracture Toughnesssupporting
confidence: 91%
“…It follows from theoretical works (e.g. Ghebrab and Soroushian [11]) that CH crystal pull-out raises the values of pure C-S-H to much higher values, 16.9-283 J/m 2 , which is in relation to our findings, whereas the pure C-S-H fracture energy ranges only between 0.38-2.85 J/m 2 [11,12].…”
Section: Fracture Energy and Fracture Toughnesssupporting
confidence: 91%
“…Therefore, the homogenized thermal conductivity of cement paste can be implicitly expressed in terms of hydration degree and the thermal-conductivity values of individual phases (Table II) through Eq. (22). Figure 8(b) presents the thermal conductivity as a function of hydration degree for resulting cement pastes produced from the hydration of pure C 2 S and C 3 S clinkers at different w=c ratios (w=c ¼ 0.3 and 0.5) for saturated meso-and micropores compared with experimental measurements of Bentz [7] for cement of varying w=c ratio and curing conditions.…”
Section: Macroscale Thermal Propertiesmentioning
confidence: 99%
“…We have previously studied mechanical properties [18][19][20][21][22][23] and diffusion dynamics [24] of cement paste at the molecular level. In this paper, we focus on understanding the physical origins of macroscopic thermal properties of cement paste, starting from the atomic scale.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, increasing cement's porosity lowers its thermal conductivity, while this significantly decreases its mechanical properties. In a community driven by interest in superior strength and stiffness, [2][3][4][5] it is imperative to seek solutions that reduce the thermal conductivity of the construction material without decreasing its mechanical properties. In the glass community, researchers [6][7][8][9][10][11][12][13] have shown that both phonon-like propagating modes (propagons) and diffusive modes (diffusons) contribute significantly to the thermal conductivity.…”
mentioning
confidence: 99%